Doctrinal Legal Research in Common Law: The Good, the Bad, and the Ugly - Thilakarathna, Akalanka Nuwan; Kamani P Mathotaarachchi, (Technium Social Sciences Journal, 2025)
This article provides an in-depth analysis of doctrinal legal research in common law jurisdictions, highlighting its enduring importance, inherent limitations, and the critical debates that shape its role in contemporary scholarship. Doctrinal research, often referred to as black-letter law, is understood as the systematic study and interpretation of statutes, judicial precedents, and legal principles that form the structural foundation of common law systems. The study employs a literature review approach, drawing upon scholarly contributions from the United Kingdom, United States, Canada, and Australia, to classify doctrinal methodology into three distinct analytical categories: the Good, the Bad, and the Ugly. The Good encompasses the methodological strengths and practical utilities of doctrinal research, such as its clarity, logical coherence, and utility for legal practice and teaching. The Bad refers to systemic weaknesses and methodological constraints, including its insularity, lack of empirical grounding, and tendency to preserve the status quo. The Ugly captures critical perspectives that challenge doctrinalism’s neutrality, pointing to its potential exclusion of marginalized voices, its rigidity, and its self-validating tendencies. The analysis further situates doctrinal research in comparison with empirical and socio-legal approaches, underscoring how each answers fundamentally different questions about law’s nature, function, and social impact. While doctrinal research focuses on what the law is and how it can be systematically organized, empirical methods examine how law operates in practice, and socio-legal studies explore law’s broader social, political, and cultural dimensions. The article concludes that doctrinal legal research remains indispensable for articulating legal rules and principles. However, its future relevance depends on its capacity to adapt through methodological rigor and interdisciplinary integration. Rather than existing in isolation, doctrinal research is best understood as a complementary approach that, when combined with empirical and socio-legal methods, can provide a fuller and more nuanced understanding of law in both theory and practice.